Comparison Study between Batch and Continuous Processes to Obtain Chitosan-Based High Porous Biomaterial for Biological Applications. (15th May 2019) - Ursu, Alina Violeta; Furtuna, Diana; Requia, Laura; Larafa, Safa; de Baynast, Hélène; Michaud, Philippe; Djelveh, Gholamreza; Delattre, Cédric
Abstract : Foaming process can be monitored under batch or continuous flows conditions. In the batch process, foaming is time-dependent and the foaming efficiency is controlled by the operator. On the other hand, in the continuous process, the foaming efficiency is only monitored by gas and liquid flow rates. The aim of this work is to compare the two technologies to perform porous scaffold biomaterial based on chitosan (a biocompatible polysaccharide) as well as calcium (Ca 2+ ) and silica (SiO2 ) (two osteogenesis compounds). Diverse recipes using chitosan (CS) solution (2% (w / v )) in acetic acid (1% (v / v in distilled water)) mixed with whey protein isolate (WPI) (2% (w / v )) as natural surfactant were studied. They were supplemented or not by hydroxyapatite powder (HAp) and tetraethyl orthosilicate (TEOS). A jacketed narrow annular gap unit (NAGU) was used to perform the continuous foaming process. For all experimentations, the mixture flow rate was maintained at 30 mL min -1 . The influence of operating conditions such as gas and liquid flow rates was studied to obtain foams and final scaffold material with different densities and porosities. Some other recipes followed foaming under batch conditions. Generally, the recipes were placed in a vessel under mixing allowing the gas phase to come from the roof of the vessel. In this case, it becomes very difficult to control the density and the size distribution of bubbles in the final product. In both cases, liquid foams were analysed (density, bubble size distribution) and then freeze-dried for mechanical and porosity investigations using the dynamic mechanical analysis (DMA) system and scanning electron microscopy (SEM). It has been shown that the controlled injected gas affected the continuous phase, resulting in a lighter and higher porous structure, a more homogeneous appearance, and a more uniform distribution of osteogenesis components compared to one obtained using batch operation. The obtained porous materials exhibited good properties (porosity, interconnectivity, and good HAp and silica distribution) and potential for future bone regeneration applications.